Better performance of four‐dimension computed tomography as a localization procedure in normocalcemic primary hyperparathyroidism. Issue 4 (15th April 2018) - Cunha‐Bezerra, Phelipe; Vieira, Ricardo; Amaral, Fernando; Cartaxo, Henrique; Lima, Túlio; Montarroyos, Ulisses; Bandeira, Francisco
Abstract: Introduction: The multi‐phase or four‐dimensional computed tomography (4D CT) has emerged as a promising technique for preoperative localization of parathyroid lesions in patients with primary hyperparathyroidism (PHPT), but little is known about its accuracy in patients with normocalcemic primary hyperparathyroidism (NPHPT). Methods: A total of 18 patients diagnosed with PHPT underwent three methods of preoperative localization (4D CT, TC‐99‐Sestamibi scintigraphy and ultrasonography). After surgery, the results of imaging were compared with operative findings, pathological and biochemical data to evaluate the sensitivity and of each localization procedure. Results: In NPHPT the sensitivity for identifying the parathyroid lesion, according to presentation of PHPT (hypercalcemic or normocalcemic), was better with 4DCT in comparison to USG and scintigraphy. In these patients, the sensitivity for lateralization was as follows: USG: 22% (95% CI 0–44.9), scintigraphy: 11.1% (95% CI 0–31.6), 4DCT: 55.6% (95% CI 23.1–88). In hypercalcemic patients the results were as follows: USG: 58.3% (95% CI 30.4–86.2), scintigraphy: 75% (95% CI 50.5–99.5), 4DCT: 75% (95% CI 50.5–99.5). There was a poor agreement between the three procedures in the identification of the parathyroid lesions, with Kappa coeficients of 0.292 and 0.01 for scintigraphy and 4DCT, respectively, in comparison to USG. Conclusion: Our data showed that 4DCT had a better performance as a preoperative localization procedure of the parathyroid lesion in patients with NPHPT.